Formulasi teh fungsional dari kombinasi daun kelor (Moringa oleifera) dan daun sirsak (Annona muricata) - Jaya, Pingkan Mutiara; Kustiani, Ai; Puteri, Hidayatusy Syukrina (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Iron deficiency is a major nutritional problem in Indonesia, impacting immunity, productivity, and concentration, particularly in adolescent girls and pregnant women. Preventive measures through the development of functional food products based on natural ingredients rich in iron and antioxidants are an important strategy. Purpose: To formulate a functional tea from a combination of Moringa oleifera leaves and soursop leaves (Annona muricata), and to evaluate the product's organoleptic quality, iron content, and antioxidant activity. Method: This study used a Completely Randomized Design (CRD) using three formulations (F1, F2, F3) and one control. Twenty-five semi-trained panelists conducted a hedonic test covering color, aroma, taste, and texture. Iron content was analyzed using Atomic Absorption Spectrophotometry (AAS), while antioxidant activity was analyzed using the DPPH method. Results: Formulation F2 (2g moringa leaves: 3g soursop leaves: 2g palm sugar) was the best formulation with the highest preference rating: color 3.56, aroma 3.44, taste 3.12, and texture 2.96 (like category). Conclusion: The formulation used has high iron content and antioxidant activity, making it a potential functional beverage to support health and prevent iron deficiency anemia.   Keyword: Iron; Moringa Leaves; Soursop Leaves.   Pendahuluan: Defisiensi zat besi merupakan masalah gizi utama di Indonesia yang berdampak pada penurunan imunitas, produktivitas, dan konsentrasi, terutama pada remaja putri dan ibu hamil. Upaya preventif melalui pengembangan produk pangan fungsional berbasis bahan alami yang kaya zat besi dan antioksidan merupakan strategi penting. Tujuan: Untuk memformulasi teh fungsional dari kombinasi daun kelor (Moringa oleifera) dan daun sirsak (Annona muricata), serta mengevaluasi kualitas organoleptik, kandungan zat besi, dan aktivitas antioksidan produk. Metode: Penelitian dengan Rancangan Acak Lengkap (RAL) menggunakan tiga formulasi (F1, F2, F3) dan satu kontrol, serta uji hedonik yang meliputi warna, aroma, rasa, dan tekstur oleh 25 panelis semi-terlatih. Kandungan zat besi dianalisis menggunakan metode Spektrofotometri Serapan Atom (SSA), sedangkan aktivitas antioksidan dianalisis menggunakan metode DPPH. Hasil: Formulasi F2 (2g daun kelor: 3g daun sirsak: 2g gula aren) merupakan formulasi terbaik dengan tingkat kesukaan tertinggi: warna 3.56, aroma 3.44, rasa 3.12, dan tekstur 2.96 (kategori suka). Simpulan: Formulasi yang digunakan memiliki kandungan zat besi dan aktivitas antioksidan yang tinggi, sehingga berpotensi menjadi minuman fungsional untuk mendukung kesehatan dan mencegah anemia defisiensi besi.   Kata Kunci: Daun Kelor, Daun Sirsak; Zat Besi.